OPTIMIZING NAIL PLATE ADHESION: A COMPREHENSIVE TECHNICAL PROTOCOL FOR SURFACE PREPARATION - Fedorenko, Zhanna (European Journal of Interdisciplinary Issues, 2025)
This study focuses on an integrated analysis of the physicochemical and biomechanical dynamics governing the adhesion of polymer coatings to the natural nail plate. It was specifically the comprehensive retrospective evaluation of 300 clinical cases that provided the empirical evidence to establish the critical importance of maintaining a 10–15% polymer buffer to preserve the integrity of the dorsal layer. This dataset confirms that the etiology of 90% of adhesion loss events is driven by violations of pre-treatment protocols rather than the qualitative properties of the materials employed. Detailed consideration is given to the mechanisms of mechanical interlocking, the correlation between surface microtopography (roughness profile) and bond strength, and the impact of secondary contamination (micro-debris, lipid impregnation) as a catalyst for cohesive failure. The concept of functional protection is introduced, establishing that the preservation of the biological substrate’s vital functions, coupled with strict operative field asepsis, serves as the exclusive determinant of the structure’s engineering stability. A unique standardized protocol is proposed to mitigate the risk of iatrogenic onychodystrophies.